Mechanical and Electrical Properties of Polylactic Acid with Aliphatic-Aromatic Polyester - Katsuyoshi Shinyama (Journal of Engineering)
Assuming an application where polylactic acid (PLA), a hard bioplastic, is used to sheath electrical wire, the author added 20 wt% of aliphatic-aromatic polyester or polybutyrate adipate terephthalate (PBAT), a soft resin, to PLA and then investigated the softened PLA’s mechanical and electrical properties. As a result of adding PBAT to PLA, Tg shifted to about 10°C lower than PLA. In addition, adding PBAT to PLA made the PLA softer and even more so at temperatures above 40°C. Furthermore, adding PBAT to PLA decreased the electric breakdown strength (EB) of the PLA by about 1 MV/cm over the temperature range of 0°C to 50°C, and EB was slightly higher than that of PVC over the temperature range of −10 to 60°C.